Анализ газометрических способов нанесения покрытия на детали запорной и регулирующей аппаратуры - Kovaliok N. S. (Новое слово в науке: перспективы развития, 2015)
shows that thermal spray techniques protective coating a large number of different species, are promising ways to plasma deposition, highlighted materials with nano-sized particles.
Keywords: запорная арматура; protective coatings; coating methods; защитные покрытия; способы нанесения покрытий; регулирующая арматура; газотермические методы; thermal spray methods; regulating units